1991
DOI: 10.1089/lps.1991.1.221
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Colon Resection: A Case Report

Abstract: The first case of a villous lesion of the colon removed by laparoscopic-guided surgery is reported. Injection of methylene blue into the lesion facilitated its access and exposure via the laparoscope. A very small skin incision allowed delivery onto the abdominal wall for resection and anastomoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
6

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 0 publications
1
46
0
6
Order By: Relevance
“…Although laparoscopic techniques were first applied to colorectal surgery in 1991, [3][4][5][6] the approach has not been widely adopted. This is largely because of concerns over the safety of these techniques in cancer surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Although laparoscopic techniques were first applied to colorectal surgery in 1991, [3][4][5][6] the approach has not been widely adopted. This is largely because of concerns over the safety of these techniques in cancer surgery.…”
Section: Resultsmentioning
confidence: 99%
“…2007;142:253-259 L APAROSCOPIC COLORECTAL surgery was introduced in clinical practice more than a decade ago. 1,2 Technical feasibility and safety of this minimally invasive procedure are now established. [3][4][5][6][7][8] Moreover, significant advantages over the open procedure have been shown in numerous studies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no prospective randomized trial has been reported. The first reports of the application of laparoscopic surgery to colon resection were in 1991 [5,12,13,15,18,22,23]. Redwine and Sharpe detailed the transanal extraction of an endometrioma of the sigmoid colon with a stapled end-to-end anastomosis [20].…”
Section: Discussionmentioning
confidence: 99%